DIAGNOSTIC PERFORMANCE AND SAFETY OF BRONCHOALVEOLAR LAVAGE IN THROMBOCYTOPENIC HAEMATOLOGICAL PATIENTS FOR ASPERGILLOSIS DIAGNOSIS: A MONOCENTRIC, RETROSPECTIVE EXPERIENCE. - Mariagiovanna Cefalo; Ermanno Puxeddu; Loredana Sarmati; giovangiacinto paterno; Carla Fontana; Daniela Nassa; Gloria Pane; Eleonora De Bellis; Raffaele Palmieri; Elisa Buzzatti; Federico Meconi; Roberta Laureana; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
Background: although bronchoalveolar lavage (BAL) measurements of galactomannan antigen (GM) seems to be more sensitive than serum testing to detect invasive pulmonary aspergillosis (IPA), a consensus on the most appropriate diagnostic threshold of the BAL GM test is still unclear. Moreover, there is uncertainty as to whether BAL is a safe procedure in patients with hematological malignancies (HM) and thrombocytopenia (TC).